2011
DOI: 10.1161/circheartfailure.110.960260
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mass Spectrometry and Clinical Assay Measurements of Circulating Fragments of B-Type Natriuretic Peptide in Patients With Chronic Heart Failure

Abstract: Background-Multiple B-type natriuretic peptide (BNP) fragments circulate in patients with heart failure (HF) but the types and relative quantities, particularly in relation to bioactive BNP 1-32, remain poorly defined. The purpose of the study was to relate clinically available BNP values with quantitative information on the concentration of pre-secretion and post-processed fragments of BNP detected by mass spectrometry. Methods and Results-Seventy Class I-IV patients were prospectively enrolled with blood dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 22 publications
1
93
0
3
Order By: Relevance
“…NT-proBNP and degradation products have a half life of several hours, and plasma BNP concentrations measured in patients with heart failure correlate best with (biologically inactive) degradation products than with the functional BNP-32 (=BNP (1-32)) [30]. Nevertheless, chronic over-secretion of BNP (including active BNP) in chronic heart failure is indisputable.…”
Section: Discussionmentioning
confidence: 99%
“…NT-proBNP and degradation products have a half life of several hours, and plasma BNP concentrations measured in patients with heart failure correlate best with (biologically inactive) degradation products than with the functional BNP-32 (=BNP (1-32)) [30]. Nevertheless, chronic over-secretion of BNP (including active BNP) in chronic heart failure is indisputable.…”
Section: Discussionmentioning
confidence: 99%
“…Although initially it was thought that there were only 2 circulating fragments of BNP, BNP 1-32 and NTproBNP 1-76, contemporary data have challenged this concept recently (23 ). Mass spectrometry analyses showed only minute amounts of circulating BNP 1-32.…”
Section: Degradation Fragments Of Bnp In Circulationmentioning
confidence: 99%
“…Another protease, peptidyl arginine aldehyde protease, can also degrade BNP, and meprin was shown to lyse BNP in animal models but not in humans (26 ). Due to BNP instability in EDTA plasma even at low temperatures, protease inhibitors in high concentrations should always be used (23 ).…”
Section: Degradation Fragments Of Bnp In Circulationmentioning
confidence: 99%
“…As a result, NT-proBNP assay is not a reliable index of the biological (natriuretic) activity of cardiac endocrine system in severe HF because the concentration of less active peptides in patients with severe HF (such as NT-proBNP and proBNP) is greatly higher than that of the active peptide BNP (Figure 1) [1,[29][30][31][32][33]. Moreover, a recent study [34] suggested that the commercial immunoassays, commonly used for NTproBNP assay, employ non-glycosylated calibrator materials and mostly antibodies directed against epitopes with potential O-glycosylation site occupancy.…”
Section: Groupmentioning
confidence: 99%
“…In addition to the peptide hormone BNP and the inactive peptide NT-proBNP, a huge numbers of other circulating peptides derived from the pro-hormone proBNP can be identified by chromatographic procedures in human plasma, including the intact and glycosylated forms of proBNP itself [29][30][31][32][33]38] (Figure 2). Furthermore, the active hormone BNP may be produced even in vivo from the circulating intact precursor proBNP through enzymatic cleavage by some plasma proteases (such as corin) [35,36,39] (Figure 2).…”
Section: Quality Specifications For An Accurate Bnp Assaymentioning
confidence: 99%